2004
DOI: 10.1002/jmv.20063
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic and molecular analysis of influenza A (H3N2) virus strains isolated from a localised influenza outbreak in South Africa in 2003

Abstract: A severe acute institutional influenza outbreak occurred in a police residential college in Pretoria amongst new recruits and staff members at the end of May 2003. The outbreak was characterised by marked illness which affected a total of 648 students, 26 of whom were admitted to hospital. Symptoms included pyrexia, severe headache, and myalgia. The attack rate per dormitory building ranged from 20 to 47%, with an overall attack rate of 34%. Throat swabs and bronchoalveolar lavage specimens were sent to the Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 16 publications
1
36
0
4
Order By: Relevance
“…RNA was transcribed to cDNA with the influenza A virus universal primer Uni12, as described elsewhere (24). The HA genes (segment 4), the NA genes (segment 6), and the M genes (segment 7) of H1N1 and H3N2 viruses were amplified with segment-specific primers as described elsewhere (3,24).…”
Section: Methodsmentioning
confidence: 99%
“…RNA was transcribed to cDNA with the influenza A virus universal primer Uni12, as described elsewhere (24). The HA genes (segment 4), the NA genes (segment 6), and the M genes (segment 7) of H1N1 and H3N2 viruses were amplified with segment-specific primers as described elsewhere (3,24).…”
Section: Methodsmentioning
confidence: 99%
“…Sporadic monitoring of influenza in other African countries has revealed outbreaks of H3N2 virus in South Africa in 2003 [28], in Madagascar in 2002 [2], and in the Democratic Republic of Congo in 2002 [2]. In addition, influenza B viruses have been reported to be circulating in South Africa, Madagascar, and Kenya [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…33 A 2006 Cochrane review of 64 studies published between 1974 and 2004 found that in homes for the elderly (with good influenza vaccine match and high viral circulation) the effectiveness of vaccines against influenza-like illness was only 23% (95% confidence interval 6% to 36%) and non-significant against influenza (RR 1.04: 95% confidence interval 0.43 to 2.51). 34 How 35 The serologic response to influenza virus vaccine also varies with the age of the recipient and previous exposure to influenza virus. 36 In primed individuals (those who have had previous exposure to influenza), vaccination with CIV induces "protective" levels of antibody against HA, which prevent infection in 89% of recipients shortly after vaccination.…”
Section: Current Influenza Vaccinesmentioning
confidence: 99%